A comparison of magnetic resonance, X-ray and positron emission particle tracking measurements of a single jet of gas entering a bed of particles. (27th January 2015) - Pore, M.; Ong, G.H.; Boyce, C.M.; Materazzi, M.; Gargiuli, J.; Leadbeater, T.; Sederman, A.J.; Dennis, J.S.; Holland, D.J.; Ingram, A.; Lettieri, P.; Parker, D.J.
Abstract: Measurements of the lengths of a single jet of gas entering a packed bed were made using magnetic resonance imaging (MRI), positron emission particle tracking (PEPT) and X-ray radiography and the results compared. The experiments were performed using a Perspex bed (50 mm i.d.) of poppy seeds: air at 298 K was admitted to the base of the bed through a single, central orifice, 2 mm in diameter. Poppy seeds (Geldart Group B, measured minimum fluidisation velocity with air at 298 K and 1 atm of 0.13 m/s and particle density 1060 kg/m 3 ) were used because of their high content of oil, which contains mobile protons and hence is suitable for MRI examination. The lengths of jet measured using the three techniques were in agreement between 50 m/s< U o <100 m/s, where U o is the superficial velocity through the orifice. Below U o =50 m/s, X-ray measurements of jet lengths were shorter than those measured using MRI. This was attributed to the minimum diameter of void, found to be 5 mm, detectable in a 50 mm bed using ultra-fast X-ray measurements. PEPT is most commonly used to calculate particle velocities, whilst jet lengths are usually calculated from determinations of voidage. However, the particle locations determined in this work by PEPT were used to calculate a fractional occupancy count, from which a jet length could be inferred. Highlights: Magnetic resonance, PEPT and X-ray radiography were used complementarily. Length of jet of gas entering bed of Group B particles via 2 mm id orifice measured. Lengths were in good agreement for orifice velocities 50–100 m/s. Technique developed to use PEPT measurements to quantify jet length.